The Development of Catholicism in Early 20th Century Malang City - Wijaya, Daya Negri; Dhani, Arif Perwira; Rahmah, Nadya; Hartono, Hartono (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Malang City is one of the cities in the interior of Java which is often called Klein Switzerland or like a small version of Switzerland with its beautiful scenery and cool air. These conditions made Malang ideal as a target for implementing policies, one of which was the 1870 Agrarian Law and the construction of the railroad in 1876, which then increasingly developed into a city. Community mobilization was inevitable as was the arrival of the Dutch and the migration of the local population itself. The interaction that takes place presents a blend of indies lifestyle in all lines of life, one of which is the architectural field of church construction. This research aims to find out the arrival of Catholicism in Malang and its influence on the development of the local community with a focus on the Ijen Church and Kayutangan. The method used uses historical research methods consisting of heuristics, verification, interpretation, and historiography. The results showed that Catholic missionaries played an important role in the spread of Catholicism in Malang as evidenced by the establishment of the Kayutangan Sacred Heart of Jesus Church building and the Ijen Cathedral Church which still exists and has even become an iconic landmark of Malang City.